Evaluation of result of circumcision done in hospital raja perempuan zainab ii and circumcision done in the community setting - Sidik, Mohammad Hisyam (2010)
Circumcision is an important medical and ritual procedure that already performed for thousand of years. Nowadays circumcision is practised in hospital, in the community setting under clean but non sterile environment and also in the traditional way. The hazards of traditional circumcision is clearly documented, however the result of circumcision done in the community was not objectively studied. This raises the question whether such practice is safe or other recommendation should be made to improve the outcome of this important procedure. This study aims to evaluate the difference in the incidence of bleeding and infection complication of circumcision done inside hospital and outside hospital. This is a prospective study reviewing 75 circumcisions done in Hospital Raja Perempuan Zainab II and 84 circumcisions done outside hospital in Kota Bharu and Pasir Mas area. followed up one hour, three days and seven days after the circumcision. Incidence of bleeding and wound infection was recorded. Data analysis was done using SPSS software version 18.0. The incidence of wound infection of outside hospital group is higher than inside hospital group (22.6% vs 9.3% p=0.024) with relative risk of 2.42. The incidence of bleeding is no different between outside hospital and inside hospital group (4.8% vs 6.7% p=0.736). This study proves that circumcision performed outside hospital has more risk of developing wound infection compared to circumcision done inside hospital. However the bleeding complication is identical in between these two groups.